Pembuatan dan Karakterisasi Kertas Kemasan Berbasis Ampas Kunyit dan Jahe Merah dengan Variasi Konsentrasi Natrium Hidroksida: Preparation and Characterization of Packaging Paper Based on Turmeric and Red Ginger Pulp with Varying Concentrations of Sodium Hydroxide - Jannah, Devia Fataya Miftahul; Febryanti, Chyntia Wahyuni; Alfiah, Diana; Huwaida, Melina Rahma; Marhani, Della Agustia; Riniati, Riniati (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2023)
The production of herbal beverages such as ginger, turmeric, and other spices generates waste that is commonly discarded. The cellulose content in red ginger is about 60-80%, and in turmeric, it is 50%. The high cellulose content makes red ginger and turmeric waste suitable for use as raw materials for paper production. The objective of this research is to determine the optimum conditions for making paper based on red ginger and turmeric waste. The pulp formation process was carried out using the Semi-Mechanical Method, which involves the addition of chemical solutions and grinding, on a mixture of turmeric and red ginger waste (60:40) with variations of NaOH concentration at 8%, 10%, and 13% (w/v). The papermaking process began with refining and drying the waste, cooking the pulp, adding water and kaolin filler, and then printing. Characterization included antibacterial testing, tensile strength, and grammage. Based on the pulp characterization results at the optimum NaOH concentration of 8%, the moisture content was 8.89%, cellulose content was 49.28%, and lignin content was 9.28%. These parameters comply with the national standard (SNI) for packaging paper. The paper characterization results showed a tensile index of 2.12 Nm/gram, an antibacterial inhibition zone of 5 mm, and a grammage of 13 g/m2. This research indicates that the NaOH concentration influences the moisture, cellulose, and lignin content. Furthermore, based on the characterization results, paper made from turmeric and ginger waste has the potential to be used as antimicrobial packaging paper.